Comunicação entre enfermeiros e idosos na atenção primária de saúde: uma análise à luz da teoria de Peplau - Silva, Juliana Paiva Góes da (2012)
It is possible to integrally comprehend the patient through the communication in the relationship between the nurse and the patient. In this way, this professional tries to understand the patient s view of the world and their attitudes. For the user of the basic attention, the link consolidates through good communication, whenever the nurse creates empathy by good reception, respect, care, attention and thus the patient feels safe and confident. To the extent of the elderly population, it is known that it has been growing significantly day by day and that society needs to look for adaptations to comply with their necessities. It is also known that many elderly seek assistance in the primary attention to fulfill the process of their health state since this service is near the community and facilitates their access. The main purpose of this study is to analyze the communicative process between nurses and the elderly in the health primary attention based on the theory by Peplau. This research has a descriptive nature and a quantitative approach. It was accomplished by some shootings in the nursing consultations in health basic units in João Pessoa Paraíba Brazil. Thirty-two nurses connected to the Family Health Strategy made part in the research as well as thirty-two elderly listened by the nurses during the collection period from May to September 2011. Communication experts have also participated in the research; they have validated the instrument for analysis of communication according to Peplau and the judges analyzed the shootings. The data have been processed in the Statistical Package for Social Sciences Program (SPSS) 18.0 and analyzed through descriptive and inferential statistics and unvaried and bivariate tables with relative frequency and percentages. Were considered the ethical observances. They may be found in the regulatory guidelines and norms which involve human beings Resolution 196/96 from the Health National Counsel, mainly in what it concerns to the free agreement by the participants and the secret of the data. In this study it was observed that the communication between the nurses and the elderly was classified (in a general way) as fine. This reflects the principles of the primary attention to the health which prioritizes the bond formation between the professionals and the community by a relationship based on trust and empathy, since the users listened by this service should be seen continuously by the health staff. However there are still some blanks that must be filled in so that the excellence in the observed interactions. In this sense, as the nurses search for the improvement of the quality of the interactions, the communication between the nurse and the elderly in the primary attention will get better and more adequate for the fulfillment of the assistance of the population what cooperates for the users satisfaction related to the nursing assistance. For this, it is necessary to look for the professional qualification focused in the attention to the elderly as well as the scientific knowledge turned to the strategies that facilitate the communication.